Comparative study on numerical simulation based on CALPUFF and wind tunnel simulation of hazardous chemical leakage accidents - Zhang, Rongqian; Li, Mei; Ma, Hancong (Frontiers in Environmental Science, 2022)
CALPUFF, as a Lagrangian puff modeling system, is mostly used in the fields of atmospheric environment research and risk assessment. CALPUFF performs well for short term and short range release scenario over complex terrain, as well as long term and long range transportation. Therefore, this article uses the CALPUFF model to simulate a toxic gas leakage accident in a hazardous chemical plant in urban area, focusing on the influence of local buildings. Wind tunnel experiments are performed in accordance with the CALPUFF experiments to assess the model’s accuracy in cases of chemical leakage accidents. The results of wind tunnel experiment are superimposed on the map of CALPUFF calculation, and the quantitative analysis is also performed. The comparation results show that the simulation results of CALPUFF are mainly affected by factors such as wind direction, wind speed, and the complexity of the surface environment. With less influence of buildings, such as south and north wind, the CALPUFF simulation is consistent with the wind tunnel experiment, while under the east wind, the consistency is significantly lower due to the influence of buildings. In addition, it is found that the wind tunnel experiment is more accurate in the near field of pollution source, while CALPUFF is more suitable for simulating the overall trend of the gas dispersion. The comparation and evaluation of the capabilities of different methods on gas dispersion simulation are helpful to guide the emergency response during hazardous chemical leakage accidents.